Development Of Qr Code-Based Digital Audio Tourism As A Cultural Education Media In Sumpang Bita Archaeological Park - Dharu Cahyoaji Sasongko; Jarwinda; Teny Sylvia; Idra Herlina (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
The Sumpang Bita Archaeological Park in Pangkep Regency, South Sulawesi, is a prehistoric rock art site with important archaeological value, but interpretation facilities are still limited, preventing visitors from gaining adequate contextual understanding. This study aims to develop a QR code-based digital audio tour model as an educational, inclusive, and accessible interpretation medium for the Sumpang Bita Archaeological Park. The methods used included field observations with interviews with 20 visitors, the design of bilingual narrative content (Indonesian-English), and the implementation of the system through the installation of QR Codes at strategic points on the site. Survey results showed that 70% of respondents were unaware of the site's primary historical value, 65% considered supporting facilities very inade quate, and 100% stated that they needed additional guidance. The implementation of the audio tour system has been proven to improve access to information, expand audience reach, including groups with disabilities and speech impairments, and support the trend of digitalization of cultural tourism. While initial trials are limited by their small scale and internet network constraints, this model offers a cost-effective solution that can be replicated at other open archaeological sites. Thus, the development of QR code-based audio tours through the National Community Service Program provides a significant contribution to the preservation of cultural heritage while strengthening the educational experience and community involvement in the conservation of prehistoric sites.